(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2009)
This report includes four regional reviews on environmental impact assessment (EIA) and monitoring in aquaculture in Africa, Asia-Pacific, Europe, Latin America and North America; a special study on EIA as applied to salmon aquaculture; and a global review and synthesis report which draw on the findings of the review papers, covering relevant information from more than 35 countries. In addition, this document provides the report of a workshop on the subject held at FAO headquarters in Rome in September 2008.
Keywords: Thủy sản,Aquaculture; Khía cạnh môi trường,Environmental aspects